INOVASI NUGGET SEHAT GANIL KEKO : SOLUSI STUNTING DAN KETAHANAN PANGAN - Fadilla, Alya Noor; Putri, Aulia Bareta; Niandra, Dita; Cavalera, Jazzy; Rahayu, Tilafatiyah (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
This research is motivated by the development of instant food in the form of nuggets that are in great demand by the public. Unfortunately, nuggets do not have nutritional content that meets nutritional needs. Meanwhile, Wonogiri has a variety of natural resources that have not been utilised optimally. Starting from the maritime sector and the agricultural sector. The availability of cassava, as the largest food commodity in Wonogiri, is less attractive to young people. The purpose of this research is to utilise cassava flour into an innovation that is attractive to various groups and combine it with moringa leaves, koro pedang flour and tilapia as a large fishery production in Wonogiri. The research method used is experimentation through several processes. Starting from cleaning tilapia meat in the first stage. In the second stage, we sifted cassava flour and koro pedang flour. In the third stage, tilapia meat is mashed together with moringa leaves and spices. The fourth stage is steaming the nugget dough until cooked. This research was conducted to develop an innovation of modified cassava flour together with tilapia meat, moringa leaves, and koro pedang flour into a healthy Ganil Keko nugget product. This new innovation is expected to optimise natural resources in Wonogiri, help the government's programme to prevent stunting, and help economic sustainability to improve the welfare of the community. Data collection used is a questionnaire distributed to SMA Negeri 2 Wonogiri school residents, namely fellow students, security guards, staff and teachers as respondents as many as 16 people with 10 people answering questionnaire questions that have been provided through an online platform and 6 others interviewed directly. The results obtained showed that Ganil Keko healthy nuggets have several nutritional contents based on laboratory tests that we conducted at the UESBE laboratory, it is known that the contents contained in it include 52.42% water content, 2.11% ash content, 1.79% fat content, 11.83% protein content, 31.91% carbohydrates, and 4.41% crude fibre.